IDENTIFICATION OF HOST PLANT RESISTANCE TO BEAN COMMON MOSAIC VIRUS (BCMV) IN COWPEA (VIGNA UNGUICULATA L. WALP.) GENOTYPES - N. MANJUNATHA,; P. RUDRASWAMY,; K.T. RANGASWAMY,; N. NAGARAJU,; H.A.PRAMEELA, (The Bioscan, 2015)
One hundred cowpea genotypes screened under field condition during kharif, 2013 and 2014 and further evaluated at greenhouse condition by artificial sap inoculation. The disease incidence varied from 0 to 60 % and 0 to 63.33 % in field and artificial condition respectively. The most of the genotypes studied were categorized as moderately resistant to moderately susceptible. Three out of hundred genotypes appeared to be immune (IC- 8966, V-5 and IC-202782) under both in field and artificial condition. The genotypes showed immune and resistant reaction would be utilized as donors to develop BCMV resistant varieties.